RELATIONSHIP BETWEEN SODIUM INTAKE WITH HYPERTENSION LEVELS IN PATIENTS IN THE REGION DIAMOND PUSKESMAS WORK BOALEMO DISTRICT - Sry Haslinda Mahadjani; Rita Amini Warastuti; Sofyan Tambipi (Journal of Hulonthalo Service Society (JHSS), 2023)
Hypertension is a big problem not only in western countries but also in Indonesia, hypertension is suffered by one billion people worldwide and it is estimated that in 2025 it will increase to 1.5 billion people. Intake of nutrients that also affect blood pressure is sodium. This study aims to determine the relationship between sodium intake and the level of hypertension in patients in the working area of Berlian Health Center, Boalemo Regency. The method in this study used a cross sectional research design to see if there is a relationship between sodium intake and the level of hypertension in patients in the working area of the Berlian Health Center, Boalemo Regency . The results showed normal sodium intake with mild hypertension in 12 people (31.5%), moderate in 4 people (10.5%) and 1 person in weight (2.6%), while sodium intake was more with mild hypertension in 4 people (10.5%), moderate as many as 12 people (31.5%) and heavy as many as 5 people (13.1%). It can be concluded that there is a significant relationship between sodium intake and the level of hypertension in patients in the working area of the Berlian Health Center, Boalemo Regency, with a value of p=0.002 (p< 0.05 ).